Cyclic AMP-Responsive Element Modulator α Polymorphisms Are Potential Genetic Risks for Systemic Lupus Erythematosus. (27th October 2015) - Guo, Qian; Chen, Xuyong; Du, Yan; Guo, Jianping; Su, Yin
Abstract : To investigate whether the cyclic AMP-responsive element modulator α ( CREMα ) polymorphisms are novel susceptibility factors for systemic lupus erythematosus (SLE), four tag SNPs, rs1057108, rs2295415, rs11592925, and rs1148247, were genotyped in 889 SLE cases and 825 healthy controls. Association analyses were performed on whole dataset or clinical/serologic subsets. Association statistics were calculated by age and sex adjusted logistic regression. The G allele frequencies of rs2295415 and rs1057108 were increased in SLE patients, compared with healthy controls (rs2295415: 21.2% versus 17.8%, OR 1.244, P = 0.019 ; rs1057108: 30.8% versus 27.7%, OR 1.165, P = 0.049 ). The haplotype constituted by the two risk alleles "G-G" from rs1057108 and rs2295415 displayed strong association with SLE susceptibility (OR 1.454, P = 0.00056 ). Following stratification by clinical/serologic features, a suggestive association was observed between rs2295415 and anti-Sm antibodies-positive SLE (OR 1.382, P = 0.044 ). Interestingly, a potential protective effect of rs2295415 was observed for SLE patients with renal disorder (OR 0.745, P = 0.032 ). Our data provide first evidence that CREMα SNPs rs2295415 and rs1057108 maybe novel genetic susceptibility factors for SLE. SNP rs2295415 appears to confer higher risk to develop anti-Sm antibodies-positive SLE and may play a protective role against lupus nephritis.